2017
DOI: 10.1038/ncomms13882
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus has a genetically determined lymphotropism through co-receptor B7.2

Abstract: B-cell infection by hepatitis C virus (HCV) has been a controversial topic. To examine whether HCV has a genetically determined lymphotropism through a co-receptor specific for the infection by lymphotropic HCV, we established an infectious clone and chimeric virus of hepatotropic and lymphotropic HCV strains derived from an HCV-positive B-cell lymphoma. The viral envelope and 5′-UTR sequences of the lymphotropic HCV strain were responsible for the lymphotropism. Silencing of the virus sensor, RIGI, or overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 81 publications
3
30
0
Order By: Relevance
“…Similar to HPgV-2, HPgV can replicate in PBMCs, although it appears to be pan-lymphotropic and can infect multiple mononuclear cells including CD4 + T cells, CD8 + T cells, B cells, monocytes, and NK-cells [35,36]. Our results also show the infection and replication of HCV in B lymphocytes, which is consistent with earlier reports by Chen et al, who have determined the lymphotropism of HCV by using cellular protein B7.2 as co-receptor [37]. Wang et al reported that the association of HCV with B cells occurs mainly through the interaction of complement receptor 2 (CD21) and the CD19/CD81 complex [38].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to HPgV-2, HPgV can replicate in PBMCs, although it appears to be pan-lymphotropic and can infect multiple mononuclear cells including CD4 + T cells, CD8 + T cells, B cells, monocytes, and NK-cells [35,36]. Our results also show the infection and replication of HCV in B lymphocytes, which is consistent with earlier reports by Chen et al, who have determined the lymphotropism of HCV by using cellular protein B7.2 as co-receptor [37]. Wang et al reported that the association of HCV with B cells occurs mainly through the interaction of complement receptor 2 (CD21) and the CD19/CD81 complex [38].…”
Section: Discussionsupporting
confidence: 92%
“…HCV is not only a hepatotropic but also a lymphotropic virus, and this finding has been supported by the results of several reports that demonstrated the association of HCV with B cells both in vitro and in vivo. 11,20,21 Furthermore, our previous studies indicated that HCV 22 In this study, we confirmed that HCV RNA was detected in B cells of 83.3% and 50% of CH-C patients with G1 and G2, respectively, as previously described (Table 1). 11,14 This result suggested that HCV G1 was more lymphotropic than HCV G2;…”
Section: Discussionsupporting
confidence: 90%
“…The recent finding that a co-stimulatory receptor B7.2 (CD86) is involved in the infection of human memory B cells by the abovementioned HCV SB strain [66] substantiated the involvement of a hepatocyte-distinct receptor in HCV lymphotropism [87] ( Table 1). The study showed that the virus E1E2 envelope and 5′-UTR sequences determine lymphotropism of the SB strain and that silencing of the virus sensor retinoic acid-inducible gene I (RIGI) or overexpression of micrcoRNA-122 permitted the persistence of viral replication in B cells.…”
Section: An Important Finding Toward the Recognition Of Virological Dmentioning
confidence: 79%